2020
DOI: 10.1002/pd.5781
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on rapid exome sequencing as a diagnostic test for multiple congenital anomalies on fetal ultrasound

Abstract: Objective Conventional genetic tests (quantitative fluorescent‐PCR [QF‐PCR] and single nucleotide polymorphism‐array) only diagnose ~40% of fetuses showing ultrasound abnormalities. Rapid exome sequencing (rES) may improve this diagnostic yield, but includes challenges such as uncertainties in fetal phenotyping, variant interpretation, incidental unsolicited findings, and rapid turnaround times. In this study, we implemented rES in prenatal care to increase diagnostic yield. Methods We prospectively studied 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Other studies suggest clinical impact or influence on management in 26%-70% [13,14,25], however number of ongoing pregnancies at time of PES and resulting impact is smaller in these studies and the exact definition of clinical impact and management varies.…”
Section: Accepted Articlementioning
confidence: 78%
See 1 more Smart Citation
“…Other studies suggest clinical impact or influence on management in 26%-70% [13,14,25], however number of ongoing pregnancies at time of PES and resulting impact is smaller in these studies and the exact definition of clinical impact and management varies.…”
Section: Accepted Articlementioning
confidence: 78%
“…Molecular diagnosis in cases of structural malformation allows for greater diagnostic accuracy and can have implications for management of pregnancy; whilst studies are limited in this area, decision making has reportedly been impacted in up to 70% [13][14][15][16].…”
Section: Accepted Articlementioning
confidence: 99%
“…The additional information provided by WGS allowed precise determination of the risk of recurrence and could guide clinical management. However, the cost and data analysis challenges for applying WGS in prenatal diagnosis should not be ignored, and six fetuses with trisomy 21/18/13 who did not undergo serum screening or noninvasive prenatal screening (NIPS) were identified by WGS in our study, reminding us to perform a reliable, rapid, and cost-effective test, such as quantitative fluorescence polymerase chain reaction (QF-PCR) [ 31 ], to exclude common fetal chromosomal aneuploidies before performing WGS, especially for fetuses that did not undergo serum screening or NIPS, which seemed to be a more reasonable test path in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It may not only provide a prognosis that allows parents to make better informed choices about continuing or terminating the pregnancy, where termination is legally possible in China until 28 weeks of gestation and is possible after this time under exceptional circumstances, but also may help the obstetrician determine the best obstetric management, such as the delivery mode, and help the neonatologists in optimizing neonatal care. Recently, the procedure of simultaneous detection of CNVs and SNVs/indels following normal QF-PCR results has been applied in prenatal diagnosis [19]. In our cohort of study, only 16 cases with ultrasound anomalies were found in the early gestation (≤14 weeks), while 67 fetuses were found in the second trimester and even in the third trimester.…”
Section: The Need Of Simultaneous Detection Of Cnvs and Snvs/indels Fmentioning
confidence: 84%